Antivirals for Respiratory Viral Infections: Problems and Prospects - Liu, Qiang; Zhou, Yuan-hong; Ye, Feng; Yang, Zhan-qiu (Seminars in Respiratory and Critical Care Medicine, 2016)
In the past two decades, several newly emerging and reemerging viral respiratory pathogens including several influenza viruses (avian influenza and pandemic influenza), severe acute respiratory syndrome coronavirus (SARS-CoV), and Middle East respiratory syndrome coronavirus (MERS-CoV), have continued to challenge medical and public health systems. Thereafter, the development of cost-effective, broad-spectrum antiviral agents is the urgent mission of both virologists and pharmacologists. Current antiviral developments have focused targets on viral entry, replication, release, and intercellular pathways essential for viral life cycle. Here, we review the current literature on challenges and prospects in the development of these antivirals.
Keywords: respiratory virus; antiviral; entry; replication; pathway